(untitled) (Journal of Technology and Operations Management, 2020)
This paper presenting the findings from a case study conducted on the quality management principles in a Malaysian’s SMEs food and beverages. The objective of this research is to determine and identify the quality management principles towards the organization performance in the XYZ Industry Sdn. Bhd. In order to achieve the objective, a case study was carried out by conducting in-depth interviews with the top managers. The findings show out about a number of quality management principles have been identified as contributors towards organization’s performance. Since this research only focuses on a SMEs and beverage industry (traditional herbs drinks), therefore, the findings could be used to generalize within the similar business in the similar industry. The paper emphasizes that the implementation of quality management principles can be used as a framework to improve organization’s performance.